STRATEGI KEPEMIMPINAN DALAM MENINGKATKAN KINERJA KARYAWAN BUMD PD. SELAPARANG AGRO LOMBOK TIMUR - Salmukin, Salmukin; Hadiyati, Ernani; Muawanah, Umi (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2023)
The aim of this research is to explore and describe leadership strategies in improving the performance of BUMD PD Selaparang Agro employees, East Lombok Regency. In this research, researchers used descriptive qualitative research where the presentation of the data was done by describing the data in the form of words and language. Data collection techniques use observation, interviews and documentation. The data analysis method uses stages starting from data reduction, data presentation and verification. Research results Leadership strategies in improving employee performance in PD. Selaparang Agro does several things, namely: 1) Building good communication with employees by briefing every morning and open communication. 2) Provide motivation to employees. 3) Provide comparative study opportunities in order to increase employee experience, skills and abilities at work. 4) Apply discipline. 5) Give rewards or awards to employees who achieve achievements.